Avaliação do cloreto de cálcio por via intratesticular como método de esterilização química em bovinos - Pereira, Lucas de Freitas (2011)
This study aimed to evaluate the effect of a single intratesticular injection of a solution based on calcium chloride for chemical sterilization in bovines. Were utilized 24 young adult animals distributed in 3 groups (n = 8/group), according to the concentration of calcium chloride: Group CC20 (n = 8), Group CC30, and Group CC40. All formulations contained 0.5% dimethylsulfoxide, the volume administered was 10 mL of distilled water for all groups. The animals were evaluated (serum testosterone concentrations, body weight, testicular measurements, clinical signs, behavior, testicular ultrasound and histopathology of the testicles) for 45 days after administration of calcium chloride, and submitted to the conventional castration. Testicular fragments were taken for preparation of histological slides. The body weight did not change in the evaluated moments. No decrease was observed in the values of serum testosterone, however there was a significant increase in scrotal circumference and testicular volume, peaking at 2nd and 3rd days after product application and return to the pre-application until 45 days. At no time were observed signs of sensibility in the scrotum, but after administration of calcium chloride the testicles showed adherence, swelling and stiff consistency. No change in behavior was noted. Ultrasound examination revealed loss of integrity of the median raphe, with cavity formation and alteration of testicular echotexture. In histological evaluation, there was a similar degree of destruction, both in the seminiferous tubules and interstitium, but greater intensity was observed in the samples of CC40. Under the conditions of the study concluded that calcium chloride associated with dimethylsulfoxide can be used as a method of chemical sterilization in bovines.